Investing in Influence: How Minority Interests Can Prevail in a Democracy - Stergios Skaperdas; Samarth Vaidya (Center for Economic Studies and ifo Institute (CESifo), 2021)
How can the West's economic and political polarization be explained? We argue that persuasive lobbying at various levels of government leads to systematic deviations of policies from those desired by the majority. Implemented policies diverge from the majority position despite centripetal forces that induce interest groups to select positions closer to that majority position. Resources, organization, and cognitive biases can induce one-sided outcomes. When we allow for long-term lobbying infrastructure investments in a simpli_ed tax-and-spend model, the deviations between majority desires and implemented policies are even larger than those in the absence of long-term investments.
Keywords: D72; D73; D78; H20; 330; interest groups; lobbying; polarization; persuasion; regulatory capture